Long-Term Abnormalities of Lipid Profile After a Single Episode of Sepsis - Felici, Nicholas; Liu, Da; Maret, Josh; Restrepo, Mariana; Borovskiy, Yuliya; Hajj, Jihane; Chung, Wesley; Laudanski, Krzysztof (Frontiers in Cardiovascular Medicine, 2021)
Background: Acute disturbances of the lipid profile are commonplace during acute sepsis episode. However, their long-term persistence has not to be investigated despite pivotal role of dyslipidemia in several comorbidities excessively noted in sepsis survivors (stroke, cardiomyopathy). Methods: A total of 9,861 individuals hospitalized for a singular episode of sepsis between 2009 and 2019 were identified from electronic medical records. Lab measurements of total cholesterol (Tchol), high-density lipoprotein (HDL-c), low-density lipoprotein (LDL-c), very low-density lipoprotein (VLDL), triglycerides (TG), lipoprotein(a) [Lp (a)], apolipoprotein B (ApoB), and C-reactive protein (CRP). The data were examined as baseline values before sepsis, during hospitalization, and <3 months, 3–6 months, 6–12 months, 1–2 years, and more than 2 years from initial sepsis. Results: Significant reductions in HDL-c (HDLbaseline = 44.06 vs. HDLsepsis = 28.2; U = −37.79, p < 0.0001, Cohen's d = 0.22) and LDL-c serum levels were observed during and up to three months post sepsis, with females much less affected. In contrast, male subjects had derangement in HDL present for up to two years after a singular septic episode. Total cholesterol levels were slightly yet significantly elevated for up to two years after sepsis. TG were elevated up to one year [TGbaseline = 128.26 vs. TGsepsis = 170.27, t(8255) = −21.33, p < 0.0001, Cohen's d = 0.49] and normalized. Lp(a) was elevated up to two years after initial episode [Lp(a)baseline = 24.6 ± 16.06; Lp(a)sepsis−2year = 8.25 ± 5.17; Lp(a)morethan2years = 61.4 ± 40.1; ANOVA F(2, 24) = 7.39; p = 0.0032]. Response to statin therapy was blunted in sepsis survivors for several years after sepsis resolution. Significant drop-out in prescription of statins and niacin after sepsis was observed. Serum high sensitivity C-reactive protein was elevated for up to five years after sepsis resolution (H [6;1685] = 502.2; p < 0.0001). Discussion: Lipid abnormalities persisted long after the initial septic insult suggesting potential role in accelerating atherosclerosis and other abnormalities. In addition, sepsis seems to blunt statin effectiveness. Additionally, a significant and unexplained drop in statin use was seen in post-septic period. Conclusions: Our study suggests that persistent derangements of lipid profile components for up to two years after sepsis may be associated with altered risk of atherosclerosis-related events among sepsis survivors.